(untitled) (The Pakistan Development Review, 1995)
This study is an attempt to determine the poverty-line and the incidence of poverty in Pakistan by using data of the latest Household Integrated Economic Survey: 1990-91. The study uses a different approach. and methodology in respect of earlier studies of the subject. The approach is that of the "Basic Needs", which defines the poverty-line in terms of minimum expenditure on all needs, food as well as non-food. The methodology used in estimating the minimum expenditure on various needs is based on the "Extended Linear Expenditure System (ELES)". For the year under review, the total poverty-line was estimated at Rs 374 per capita per month, with the food poverty-line at Rs 191. A comparison with the income levels reported in the Survey revealed that roughly 47 percent population had an income less than this threshold level expenditure on all needs, the shortfall or gap being almost 25 percent. The proportion of population with an income less than the threshold expenditure on food alone was found to be 10 percent. In certain respects, the results were quite different, quantitatively as well as qualitatively, from those of the earlier studies.